2020
DOI: 10.3390/nu12051495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 3-Week In-Hospital Body Weight Reduction Program on Cardiovascular Risk Factors, Muscle Performance, and Fatigue: A Retrospective Study in a Population of Obese Adults with or without Metabolic Syndrome

Abstract: Background. In clinical practice, there is the diffuse conviction that obese subjects with metabolic syndrome may be more difficult to treat. Objectives and Methods. The aim of the present study was that to investigate the effectiveness of a 3-week in-hospital body weight reduction program (BWRP) in a large population of obese subjects with and without metabolic syndrome (n = 1922; 222 men and 1700 women, age range 18–83 yr). Outcomes such as body mass index (BMI), total (TOT) and HDL cholesterol, systolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…The treatment of obesity requires lifestyle intervention, behavioral therapy and energy deficit achieved throughout caloric restriction and physical exercise ( 4 ) in order to reduce body weight and correct wrong habits. In this context, residential body weight reduction programs (BWRP) have been demonstrated to be an effective strategy to counteract this condition and its associated comorbidities, due to their multidisciplinary approach ( 5 , 6 ). During BWRP, the prescription of a correct diet plan is essential to ensure a proper and gradual weight loss and to determine improvements of body composition and metabolic parameters ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of obesity requires lifestyle intervention, behavioral therapy and energy deficit achieved throughout caloric restriction and physical exercise ( 4 ) in order to reduce body weight and correct wrong habits. In this context, residential body weight reduction programs (BWRP) have been demonstrated to be an effective strategy to counteract this condition and its associated comorbidities, due to their multidisciplinary approach ( 5 , 6 ). During BWRP, the prescription of a correct diet plan is essential to ensure a proper and gradual weight loss and to determine improvements of body composition and metabolic parameters ( 5 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This remarkable finding was further documented by the more frequent medical supervision in responsive subjects, i.e., children and adolescents with obesity having a weight loss (∆BMI) <−5 kg/m 2 , which represents a very stringent cut-off, when compared to the weight loss induced on average by our in-hospital 3-week BWRP (i.e., about −2 kg/m 2 in terms of ∆BMI) [16][17][18].…”
Section: Discussionmentioning
confidence: 52%
“…It is noteworthy that, in the present study, weight loss was higher in children and adolescents with metabolic syndrome than those without, although medical supervision was quantitatively the same. Since we have demonstrated that the effectiveness of an (isolate) BWRP is similar in obese subjects with or without metabolic syndrome [17], this would suggest that the "qualitative" features of medical supervision administered to obese adolescents with metabolic syndrome represent a valuable therapeutic component for the success of any intervention in this group of patients who, by contrast with those with simple obesity, need more aggressive clinical management, including more careful medical supervision [28].…”
Section: Discussionmentioning
confidence: 97%
“…Medical management of metabolic syndrome does not include only pharmacological interventions. In fact, the administration of a BWRP to obese patients has been demonstrated to be extremely effective in improving most of the cardiometabolic conditions underlying the metabolic syndrome, such as dyslipidemia, glucose intolerance, and hypertension [ 7 , 8 ]. In this respect, the early admission of obese patients to a BWRP (third level of health care) might be a valid solution of public health to interrupt the vicious circle referring to the natural history of metabolic syndrome [ 30 ] and the serious issues of underdiagnosis/undertreatment, which have been evidenced in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, body weight reduction programs allow us to reduce visceral obesity, improve glucometabolic homeostasis, and control hypertriglyceridemia and hypertension [6][7][8][9]; moreover, effective pharmacological interventions are available to treat dyslipidaemia, hyperglycaemia, and hypertension in clinical practice [10].…”
Section: Introductionmentioning
confidence: 99%